Legal Analysis of Unregistered Marriage Service Providers According to the Compilation of Islamic Law and Act No. 1 of 1974 on Marriage - Meilya Nur Prianjani; Sugeng; Esther Masri (Fakultas Hukum Universitas Widya Mataram, 2022)
The news of a valid marriage or a series marriage is often controversial, resulting in uncertainty of the marriage status, which has a negative impact on the parties involved, both wife, husband and child. Where it is explicitly stipulated in the Compilation of Articles 5 and 6 that marriages must be recorded before the Marriage Registrar (PPN) and registered with the KUA. The Law No. 1 of 1974, concerning Marriages, provides that every marriage shall be recorded according to the law in force, because it shall be performed in accordance with the terms and conditions in force which shall be confirmed before the law by the marriage record. The study aims to identify and analyze the phenomenon of online series weddings in Jakarta in particular and various legal issues arising from online series wedding practices and to study the series wedding using the wedding service provider that is distributed through social media. The aim of this study is to give thought to the development of legal science especially in the field of marriage law. Based on the conclusion, the author suggests the need for public awareness to be able to understand that whatever the reason, the negative impact of serial marriages is greater than the benefits. The issue of legal marriage or serial marriage is often a controversy that leads to uncertainty about the status of the marriage, which has a negative impact on the parties involved, both wife, husband and child. Keywords: unregistered marriage, service providers